The Loss of Teacher’s Authority in Online Learning During Covid-19 Pandemic - Fitri Oviyanti; Irwan Abdullah; Zulvia Trinova; Alfurqan Alfurqan (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The Covid-19 epidemic has altered social and physical segregation policies in the field of schooling. Due to this restriction, learning is now done online instead of in person. Teachers also lost their true authority in the classroom as a result of this evolving learning practice. This study employed a qualitative research methodology. Interviews and observation are used to acquire data. The method of data analysis makes use of the theory. Interviews and observation are used to acquire data. The method of data analysis relies on Miles and Huberman's theory, which calls for gathering, reducing, and presenting data. This study demonstrates that throughout the pandemic, teachers have lost their influence over online learning. Following up on this research will need to assess how prepared teachers are to deal with shifts from traditional offline to online learning environments